Analysis of the intramolecular 1,7-lactone of N-acetylneuraminic acid using HPLC–MS: relationship between detection and stability - La Rocca, Paolo; Lavota, Ivana; Piccoli, Marco; Cirillo, Federica; Ghiroldi, Andrea; Ciconte, Giuseppe; Pappone, Carlo; Allevi, Pietro; Rota, Paola; Anastasia, Luigi (Glycoconjugate journal, 2023)
A subclass of the sialic acid family consists of intramolecular lactones that may function as key indicators of physiological and pathological states. However, the existence of these compounds in free form is highly improbable, since they are unlikely to exist in an aqueous solution due to their lability. Current analytical method used to detect them in biological fluids has not recognized their reactivity in solution and is prone to misidentification. However, recent advances in synthetic methods for 1,7-lactones have allowed the preparation of these sialic acid derivatives as authentic reference standards. We report here the development of a new HPLC–MS method for the simultaneous detection of the 1,7-lactone of N -acetylneuraminic acid, its γ-lactone derivative, and N -acetylneuraminic acid that overcomes the limitations of the previous analytical procedure for their identification.